Transcriptome sequencing–based analysis of the molecular mechanism underlying the effect of lncRNA AC003090.1 on osteoporosis - Huafeng Zhuang; Yongjun Lin; Chengye Lin; Miao Zheng; Yizhong Li; Xuedong Yao; Youjia Xu (Journal of Orthopaedic Surgery and Research)
Abstract Objective To analyze changes in the expression of osteoporosis (OP)-related genes across different bone types based on transcriptome sequencing, and to identify the key molecules and mechanisms involved in the progression of OP in order to better understand this process. Methods Ten pairs of postmenopausal patients with osteoporosis (OP) and non-osteoporotic (non-OP) volunteers were included. Transcriptome sequencing was performed on six pairs of spongy and cortical bone tissues. The expression of FOXP1 was detected using quantitative real-time PCR (RT-qPCR) and receiver operating characteristic (ROC) curves. Magnetic-activated cell sorting was conducted, and the expression levels of AC003090.1, miR-203a-3p, and FOXP1 were measured using RT-qPCR. Human bone marrow stem cells (hBMSCs) were infected with a lentivirus carrying the AC003090.1 expression plasmid. The expression levels of Runx2, Opn, and Ocn in spongy and cortical bone samples, as well as in post-infection cells, were assessed through RT-qPCR. The expression levels of GSK-3β, β-catenin, and c-Myc were evaluated by performing RT-qPCR and Western blot analysis. Result A total of 2,102 out of 2,827 differentially expressed genes (DEGs) were identified between the cortical bone samples from patients with osteoporosis (OP) and the cortical/spongy bone samples of the control group. Among these, 1,482 were significantly up-regulated, and 620 were significantly down-regulated, while 1,146 were significantly up-regulated and 1,681 were significantly down-regulated. The expression of FOXP1 in tissue and bone tissue-derived mesenchymal stem cells (MSCs) from patients with OP was significantly lower than that in patients without OP. FOXP1 levels in bone tissue (cortical bone AUC = 0.825, P = 0.01405; spongy bone AUC = 0.800, P = 0.02338) could serve as predictors of OP. In addition, the overexpression of AC003090.1 significantly enhanced the transcription levels of Runx2, Opn, and Ocn; significantly upregulated the expression levels of β-catenin and c-Myc; and inhibited the expression of GSK-3β. Transfection with miR-203a-3p mimics and FOXP1 small interfering RNA reversed the effect of AC003090.1 on GSK-3β/β-catenin/c-Myc signaling. Conclusion FOXP1, as a molecular mediator of AC003090.1, affects the GSK-3β/β-catenin/c-Myc signaling pathway and promotes the osteogenic differentiation of hBMSCs, thus playing a key role in the progression of OP.